Two new Docosia Winnertz species (Diptera: Mycetophilidae) from Transcaucasia, with DNA sequence data and updated molecular phylogeny - Kurina, Olavi; Burdíková, Nikola; Ševčík, Jan (Zootaxa, 2025)
Two new Docosia Winnertz species—D. babale sp. nov. and D. dali sp. nov.—are described from Georgia (Transcaucasia) based on both morphological and molecular characters. Both new species, described from singletons, belong to a species group characterised by details in the male terminalia: bifid gonostylus, prominent medial process bearing ramified setae at the posteroventral margin of the gonocoxites, and delimited lateral extensions of the posteroventral margin of the gonocoxite. An updated phylogenetic hypothesis of the genus Docosia based on four DNA markers (28S, ITS2, COI, COII) is proposed.